Investigating the Utility of a Mindfulness-Based Intervention with Men on Probation or Parole - Holt, Reginald Wynn (2015)
Using a mixed-method design of quantitative and qualitative approaches, this study investigated the utility of implementing an adapted version of Mindfulness-Based Relapse Prevention for Addictive Behaviors (MBRP; Bowen, Chawla, & Marlatt, 2011) with six men on probation or parole. The researcher integrated a focus on anger management into the eight MBRP sessions and taught mindfulness meditation exercises during a weekly group. Outcome variables of mindfulness, anger, and empathy were measured at baseline and immediately after the intervention. Field violation and parole revocation data were provided by the Missouri Department of Corrections 30 days following completion of the program. The participants’ overall experience was also explored through semi-structured interviews at the end of the meditation course. A six stage thematic analysis process revealed 17 themes that were categorized within five distinct categories: (a) meditation practice promoters, (b) meditation practice deterrents, (c) mindfulness skills, (d) self-regulation of thoughts, emotions, and behaviors, and (e) consideration of self and others. Due to a small sample size, the quantitative data obtained through questionnaires, inventories, and correctional system records were reported through descriptive statistics. Although statistical analyses could not be conducted, many self-reported benefits were derived from the participants’ experience learning a mindfulness-based intervention. Some, but not all, participants indicated a desire to develop their meditative practices once the on-site meditation groups were no longer available. A summary of the study, the major findings, and results related to the literature are presented. Strengths and limitations of the study, as well as implications for action by correctional system and counseling staff working with the offending population are discussed. Lastly, recommendations for future research integrating mindfulness-based programs into the treatment plan for offenders are offered